2008
DOI: 10.1002/adsc.200700458
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Bioreduction of CC Bonds using Enoate Reductases OPR1, OPR3 and YqjM: Enzyme‐Based Stereocontrol

Abstract: Three cloned enoate reductases from the "old yellow enzyme" family of flavoproteins were investigated in the asymmetric bioreduction of activated alkenes. 12-Oxophytodienoate reductase isoenzymes OPR1 and OPR3 from Lycopersicon esculentum (tomato), and YqjM from Bacillus subtilis displayed a remarkably broad substrate spectrum by reducing a,b-unsaturated aldehydes, ketones, maleimides and nitroalkenes. The reaction proceeded with absolute chemoselectivity -only the conjugated C=C bond was reduced, while isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
1
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(205 citation statements)
references
References 61 publications
11
192
1
1
Order By: Relevance
“…A similar time-dependent loss of enantiopurity for these compounds was seen with other OYEs, although it was not investigated in detail. [2,3] Since the enzymatic reaction with these substrates was complete after 24 h, we concluded that the loss of optical purity was due to racemisation of products with a stereogenic centre at Cα. The apparent rate of racemisation varied depending on the nature of the product.…”
Section: -16bmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar time-dependent loss of enantiopurity for these compounds was seen with other OYEs, although it was not investigated in detail. [2,3] Since the enzymatic reaction with these substrates was complete after 24 h, we concluded that the loss of optical purity was due to racemisation of products with a stereogenic centre at Cα. The apparent rate of racemisation varied depending on the nature of the product.…”
Section: -16bmentioning
confidence: 99%
“…This unexpected change of enantioselectivity for formation of 2-methylcyclopentanone 17b has also been reported for other OYEs, although no explanation for this observation was given. [2][3][4] In light of recent work by Stewart et al [5] it is possible that substrate 17a may bind in a 'flipped' orientation, while maintaining an optimal Cβ-FMN N5 distance and angle (105°), [21] similar to that seen for OYE1 mutant W116I. [5] PETNR proved to be highly efficient and highly stereoselective in the reduction of 2-methylmaleimide derivatives 1a-b giving the respective (2R)-products in quantitative yields and high enantioselectivities (>99% ee, Table 2 and Scheme 1c).…”
Section: Stereoselectivity Of Petnr-catalyzed Reduction Of αβ-Unsatumentioning
confidence: 99%
See 1 more Smart Citation
“…Successful attempts in the chemo-and stereoselective reduction of activated alkenes were reported by using cloned yeast OYE1 from Saccharomyces carlsbergensis, [5][6][7] , OYE2 and OYE3 from S. cerevisiae, [6][7][8] CmOYE from Candida macedoniensis; 9 and bacterial OYE homologues YqjM from Bacillus subtilis, NCR from Zymomonas mobilis; 6,10 and plant OYE homologues LeOPR1 and LeOPR3 from Lycopersicon esculentum (tomato). 10,11 The plant 12-oxophytodienoate reductase (OPR) is involved in the reduction of (9S,13S)-12-oxophytodienoate to the corresponding cyclopentanoic acid OPC-8:0 for jasmonate biosynthesis. 12 By using the cloned OPR1 and OPR3 from tomato, a striking change of stereoselectivity and a remarkably broad substrate spectrum were achieved for asymmetric reduction.…”
Section: Introductionmentioning
confidence: 99%
“…12 By using the cloned OPR1 and OPR3 from tomato, a striking change of stereoselectivity and a remarkably broad substrate spectrum were achieved for asymmetric reduction. 10,11 Although the above OYE enzymes have been biochemically well characterized, they have never been investigated for the capacity of reducing the allylic alcohol double bond in geraniol, because alcohols are not typically favored as activating groups for OYEs. 3 In our effort to broaden the applicability of plant OPR, we came across its catalytic activity of converting geraniol to citronellol as a sole product (Scheme).…”
Section: Introductionmentioning
confidence: 99%